QUATERNARY BUILD-UPS AND RHODALGAL CARBONATES ALONG THE ADRIATIC AND IONIAN COASTS OF THE ITALIAN PENINSULA: A REVIEW (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
In the Mediterranean, build-ups (created by coralline algae, Cladocora caespitosa, deep-water corals, vermetids, polychaetes and bacteria) and rhodolith beds are important hot-spots of biodiversity. Being severely threatened by anthropogenic impact and climate change, they have been included in international directives on environmental protection. This work wants to support the ongoing research on modern bioconstructions by providing further data on the long-term effects of environmental factors on these habitats. Our results are based on the analysis of the existing literature on the outcropping Quaternary successions of the Adriatic and Ionian coasts of peninsular Italy. The existing reports of build-ups and rhodalgal carbonates have been summarized in an homogeneous data-set and then studied to highlight distribution patterns in space and time. The analyses consistently outlined the importance of sedimentation rate in controlling the general distribution of build-ups and rhodalgal carbonates. The majority of the reports is concentrated south of the Gargano, where the sediment-load of the rivers is small. The majority of the reports is related to coralline algae, suggesting that they were the main carbonate producers during the period. C. caespitosa general distribution is mainly controlled by temperature, with most of the occurrences dating back to the warm periods of the late Ionian and of the Tarantian. Large build-ups of Cladocora are restricted to embayments and gulfs well-protected against storm waves. The distribution of the outcrops of deep-water corals is biased by the geological setting. A remarkable uplift is necessary to bring these corals from their original deep-water setting to elevated areas onshore. Consequently, most of the outcrops are in Southern Calabria which is characterized by a strong Quaternary uplift. Chemosynthetic build-ups, intertidal bioconstructions (made by vermetids, polychaetes or coralline algae), as well as stromatolites, are rare in the study area.